Stress and Coping Among Students Preparing For Medical Entrance Examinations (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: Medical education is a demanding one with thousands of students appearing for the entrance examinations. The preparation for the examination can take a toll on the students. Despite this virtually no studies have looked into the mental health state of these students.Material and Method: 261 students preparing for medical entrance examinations in a coaching institute were assessed using DASS-21 and Brief COPE Inventory.Results: 63.8%, 82% and 51.3% of the participants reported suffering from depressive symptoms, anxiety and stress respectively of which 8%, 23% and 1.9% reported suffering from extremely severe depression, anxiety and stress respectively. Students mostly used planning, positive reframing and active coping to cope with the stress.Conclusion: Students preparing for medical entrance suffered from considerable stress and psychological interventions need to be formulated to help them.